Microwave-assisted synthesis of Mn3O4 nanoparticles@reduced graphene oxide nanocomposites for high performance supercapacitors. (October 2015) - She, Xiao; Zhang, Xinmin; Liu, Jingya; Li, Liang; Yu, Xianghua; Huang, Zhiliang; Shang, Songmin
Graphical abstract: Highlights: Mn3 O4 @rGO nanocomposites were prepared by one-step microwave-assisted method. The growth of Mn3 O4 and the reduction of graphene oxide occurred simultaneously. Specific capacitance of the nanocomposite is higher than those of rGO and Mn3 O4 . The nanocomposites have good rate capability and cycling stability. ABSTRACT: One-step microwave-assisted synthetic route for the fabrication of Mn3 O4 nanoparticles@reduced graphene oxide (Mn3 O4 @rGO) nanocomposites has been demonstrated. The morphological structures of the nanocomposites are characterized by Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, X-ray diffraction (XRD), thermogravimetric analyses (TGA), and scanning electron microscopy (SEM), respectively. All of the results indicate that the microwave-assisted synthesis results in the growth of Mn3 O4 and the reduction of graphene oxide simultaneously in ethylene glycol-water system. The specific capacitance of the as-prepared Mn3 O4 @rGO nanocomposite is higher than those of rGO and pure Mn3 O4, which indicates the synergetic interaction between rGO and Mn3 O4 . The nanocomposites also have good rate capability and cycling stability in electrochemical experiments. This facile technique may be extended to the large scale and cost effective production of other composites based on graphene and metal oxide for many applications.